Creativity and Post Retirement Adjustment of Public Servants in Akwa Ibom State (Global Journal of Human-Social Science, 2019)
This study investigated the influence of creativity tendencies on post-retirement adjustment of public servants in Akwa Ibom State of Nigeria Two hundred and ninety-nine 299 public servants made up of two hundred and fourteen 214 males and eighty-five 85 females that resided in Akwa Ibom State were involved in the study A 42 item questionnaire titled Retired Public Servants Opinion Questionnaire RESPSOQ was used to elicit information on the retired persons feelings on creative tendencies and their post-retirement satisfaction of health social emotional and economic indices The questionnaire was pilot tested on one hundred 100 retired persons in two 2 local government areas from two 2 senatorial zones in the state A null- hypothesis that creative tendencies have no significant influence on post-retirement adjustment of public servants was tested using the analysis of variance ANOVA at 0 05 level of significance at 2 and 296 degrees of freedom
Keywords: creativity; post-retirement; retired public servants; economic indexes; akwa ibom state